Static and fatigue performance of reinforced concrete beam strengthened with strain-hardening fiber-reinforced cementitious composite. (15th November 2019) - Huang, Bo-Tao; Li, Qing-Hua; Xu, Shi-Lang; Zhang, Li
Highlights: Static and fatigue behavior of RC-UHTCC beams is investigated using a four-point bending test. With an increase in thickness of UHTCC, the fatigue life and mid-span deflection of RC-UHTCC beam increase. A simplified method is introduced to model the fatigue performance of RC-UHTCC beam. UHTCC layer can lower the tensile stress, strain localization and stress concentration of the longitudinal reinforcements. Abstract: The static and fatigue performance of reinforced concrete beams strengthened by strain-hardening fiber-reinforced cementitious composite is investigated. Two series of strengthened beam specimens are prepared with different thicknesses of the enhancement layer (40 mm and 50 mm), and three fatigue stress levels (0.9, 0.8, and 0.7) are tested. The fatigue life, mid-span deflection, and crack mode of the tested specimens are analyzed. Emphasis is placed on the fatigue response of the strain-hardening fiber-reinforced cementitious composite layer and longitudinal reinforcements. A simplified method is proposed to model the fatigue performance of the composite beam. The mechanism of the fatigue enhancement of the strengthened beam compared to a conventional reinforced concrete beam is as follows: (1) the enhancement layer physically contributes by taking part of the stress in the tension zone, and (2) the enhancement layer can lower the strain localization and stress concentration of the longitudinal reinforcements. Several methods for further improvement in the fatigue performance of reinforced concrete beams are suggested.